The burden of acute gastrointestinal illness and foodborne illness caused by five major pathogens among nondeployed active duty US Army service members 2014-2015 - Mullaney, Sara Beth, author; Salman, Mo, advisor; Hyatt, Doreene, committee member; McCluskey, Brian, committee member; Rao, Sangeeta, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.
Keywords: foodborne illness; burden of gastrointestinal illness